Human Capital, Quality of Sharia Supervisory Board and Maqasid Shariah Based Performance: Cross Country Evidence - Yadiati, Winwin; Prasojo, Prasojo; Listyorini, Inon; Rofiqah, Ifah; Putra, Rosyid Nur Anggara (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
The purpose of this study is to examine the relationship between human capital (HC), quality of the shariah supervisory board (SSB) and performance of maqasid shariah-based Islamic banks. This study uses secondary data from the Bankscope database of 2014 to 2018. The research samples comprised 75 banks from a total population of 96 banks. Using the dynamic panel regression two-step generalised method of moments (GMM), this study revealed that HC has a significant and positive influence on sharia maqasid-based performance. SSB quality has a significant and negative effect on Islamic banks' performance. These findings support the resources-based theory that assumes more efficient human capital can facilitate the achievement of better organisation performance. The results may serve as a guideline for Islamic bank managers to enhance their bank human capital as it has a positive relationship with maqasid sharia-based performance.